The Early Short Fiction of Edith Wharton $1 (BPart 2s - Wharton, Edith, 1862-1937 (Salt Lake City, UT : Project Gutenberg, 1995)
"The Early Short Fiction of Edith Wharton $1 (BPart 2" by Edith Wharton is a collection of short stories and verse written during the late 19th and early 20th centuries. This volume features a mix of enchanting narratives, including ghostly tales like "Afterward," and explorative pieces that capture the essence of life and relationships. Wharton's work delves into themes of memory, nostalgia, and the complexities of human emotion, often set against vividly described backdrops of English and American settings. The opening of the collection focuses on "Afterward," where we meet Mary and Edward Boyne, a couple who, after years of striving, settle into a rural English home named Lyng. Initially thrilled by their new life, Mary recalls a conversation with a friend about an elusive ghost in the house, shrouded in mystery and speculation. As they acclimate to their surroundings, a sense of foreboding emerges, particularly when hints of undisclosed secrets and unmentioned struggles begin to affect their relationship. The narrative sets a haunting tone, suggesting that the history of the house may intertwine with their present in ways that remain to be revealed, establishing a foundation for deeper exploration of existential themes that Wharton expertly crafts throughout her story collection. (This is an automatically generated summary.)s
Afterward $1 (BThe fulness of life $1 (BA Venetian night's entertainment $1 (BXingu $1 (BThe verdict $1 (BThe reckoning $1 (BVerse.s
Release date is 1995-08-01
Produced by John Hamm, and David Widger
Keywords: Fiction; Short stories, American